(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
Heads of sheep (n=180) and goats (n=120) slaughtered at four regions (Labraq, Shahat, Elbeida, and Masa) of Green Mountain areas in Libya were investigated for the presence of larvae of Oestrus ovis. The animals were divided into sex and age groups. The heads were cut along longitudinal and sagittal axes, and the larvae (L1, L2, and L3) were collected. The infestation rate was significantly higher in sheep (51.66%; n=93/180) as compared to goats (28.33%; n=34/120). In sheep, the rate was higher during May (100%), while in goat, it was higher during August (70%). The incidence of L1 peaked in April (90%) for sheep and October (100%) for goats, while L2 reached to maximum in May for sheep (26.95%) and goats (75%). L3 reached to peak in February (50%) for sheep, and June (25%) for goats. Mean intensity of larval burden was higher in sheep than goat, reaching to peak in June (9.1 larvae/head) for sheep and March (3.5 larvae/head) for goats. The infestation rate was significantly higher in males than females. The older animals were mostly affected as compared to younger animals. Highest infestation rate was recorded in Masa (45.83%), and the lowest rate was found in Labraq (40.27%). In conclusion, these findings may be used in designing the control strategies of myiasis in Libya. http://dx.doi.org/10.5455/javar.2015.b105